2011
DOI: 10.1097/ccm.0b013e3181fb7b5f
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal tube placement in critically ill patients: A prospective, randomized trial comparing the endoscopic technique with the electromagnetically visualized method

Abstract: In a head-to-head comparison correct jejunal tube placement using the new electromagnetically visualized method was as fast, safe, and successful as the endoscopic method in a comparative intensive care unit patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…Various combinations of key words used in the search included electromagnetic phenomena, enteral nutrition, instrumentation, gastrointestinal, point-ofcare testing, pneumothorax, and Cortrak. Fifteen published studies 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] were found that evaluated the effectiveness of an ETP device in determining tube location. These studies were reviewed for any reference to detection of bronchopulmonary placements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various combinations of key words used in the search included electromagnetic phenomena, enteral nutrition, instrumentation, gastrointestinal, point-ofcare testing, pneumothorax, and Cortrak. Fifteen published studies 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] were found that evaluated the effectiveness of an ETP device in determining tube location. These studies were reviewed for any reference to detection of bronchopulmonary placements.…”
Section: Methodsmentioning
confidence: 99%
“…3 Researchers in multiple studies have evaluated the effectiveness of an electromagnetic tube placement (ETP) device in distinguishing between tube placement in the stomach and in the small bowel. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, fewer studies have involved evaluation of the effectiveness of an ETP device in detecting bronchopulmonary placements. 1,6,11,12,14,16 Purpose This study had 2 purposes: 1.…”
mentioning
confidence: 99%
“…Moreover, the vast majority of previous studies had a single-center, retrospective, non-comparative design. Only one single-center study randomized patients to either EM-guided or endoscopic nasoenteral feeding tube placement ( 25 ). Th is study had a small sample size (66 patients) with a rather low success rate of the fi rst endoscopic procedure (36%), whereas reinsertions aft er tube-related complications or failed replacements were not reported.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, studies in surgical patients, especially those with an altered upper gastrointestinal anatomy aft er surgery, are scarce. Most studies, including the only randomized trial ( 25 ), were performed in a single-center intensive care setting.…”
Section: Introductionmentioning
confidence: 99%
“…A new electromagnetically visualised jejunal feeding tube system (CORTRAK Enteral Access System) compared favourably in a prospective randomised trial with the gold standard technique, endoscopic tube placement 2. The placement success rate of the new system was 91% with similar implantation time and safety profile, but at a much lower cost 2…”
Section: Introductionmentioning
confidence: 99%